PBFT Consensus Algorithm Based on Reputation Value Voting and Random Number Election - CHEN Runyu, WANG Lunwen, ZHU Rangang (Ji suan ji gong cheng, 2022)
Compared with Raft and Paxos, the original consensus algorithm, i.e., the Practical Byzantine Fault Tolerant(PBFT) algorithm, is mainly aimed at malicious nodes in a distributed system used to send error messages to other nodes, disturbing the normal operation of the entire system.This algorithm fundamentally solves the Byzantine problem of the system.However, the PBFT algorithm itself has the problem of a low consensus efficiency caused by an arbitrary primary node election.Meanwhile, existing improved algorithms generally have problems of a high communication complexity and centralization tendency.Aiming at these problems, an improved consensus algorithm, RN-VPBFT, is proposed based on reputation value voting and random number election.First, by adding supervision nodes, the algorithm realizes a decentralization of rights and an information transfer and ensures the safe operation of the system.A random parameter is then introduced during the process of voting to determine the initial reputation value, and thus the reputation value is no longer the only criterion for selecting the master node.All nodes that meet certain conditions have an equal chance to be selected as the master node.This can reduce the trend of system centralization.Finally, the algorithm establishes the dynamic reputation model of the nodes to distinguish between honest and malicious nodes in the system, simplify the consistency protocol of the consensus algorithm, and reduce the communication complexity of the entire algorithm.Experimental results show that, compared with the original PBFT algorithm and the existing improved PBFT algorithm based on reputation voting, the RN-VPBFT algorithm can reduce the communication complexity from O(N2) to O(N).The final difference in reputation of all honesty nodes is only 0.02, which is almost negligible.Therefore, the proposed algorithm has a lower communication complexity and better decentralization.